Extraskeletal Chondrosarcoma in a Cat - Alberti, Taina dos Santos; Aquini Fernandes Gil, Luciana; Nogueira Trindade, Andressa; Zamboni, Rosimeri; Brandão Costa, Marcela; Mano Meinerz, Ana Raquel; Brum Cleff, Marlete; Viégas Sallis, Eliza Simone (Acta Scientiae Veterinariae, 2024)
Background: Extraskeletal chondrosarcoma (CSE) is a malignant mesenchymal neoplasm, originating from soft tissues and characterized by cartilaginous formations, without primary bone involvement, being a rare variant of chondrosarcoma. This study aims to describe the clinicopathological aspects of CSE with humeroscapular location in a feline. Case: A 8-year-old male feline, of no defined breed, was treated at the Ceval Veterinary Outpatient of the Departamento de Clínicas Veterinárias (DCV), Faculdade de Veterinária (FV), Universidade Federal de Pelotas (UFPel) with a history of lameness and enlargement in the right forelimb. On physical examination, a firm mass was observed involving the scapula and humerus of the right forelimb. The mass extended to the axillary region and the feline did not show pain on palpation. Additional exams were carried out. In the imaging examination (radiography), a mineralized mass, with an undefined shape, was observed in the proximal and middle 3rd of the humerus. There were also discrete areas of bone lysis in the cortical bone of the humerus. Fine needle aspiration cytology was inconclusive. After evaluating the patient, high amputation of the limb was recommended, but the owner did not authorize the procedure, and analgesia was recommended. Three months after the 1st treatment, the animal returned with a marked increase in the lesion, hyporexia, oligodipsia and signs of chronic pain. The feline underwent new examinations and no distant metastases were observed. Due to the animal's clinical condition and severe pain, the owner opted for euthanasia. The feline's necropsy was carried out at the Laboratório Regional of Diagnóstico (LRD) at the FV/UFPel. On external examination, an increase in volume was observed in the right thoracic limb, measuring 17 cm in the longest axis involving the scapula and humerus. In sections, the tumor was firm, yellowish-white, fasciculated and multilobulated. The mass infiltrated the adjacent muscle tissue without compromising bone structures. In the histopathological evaluation, a proliferation of undifferentiated spindle cells was observed, with vesicular, pleomorphic, ovoid to elongated nuclei, evident nucleoli and eosinophilic, poorly defined cytoplasm. There were 2 mitotic figures per high-power field (Obj. 40x). A large amount of chondroid matrix was also observed among the neoplastic cells. The definitive diagnosis of extraskeletal chondrosarcoma was based on radiographic examination, macroscopic and histopathological findings. Discussion: The diagnosis of chondrosarcoma in the present case was based on histopathological findings of the neoplasm. The classification as extraskeletal was determined by imaging and anatomopathological examination, which made it possible to exclude primary bone involvement. The origin of extraskeletal chondrosarcomas is unknown, however, as with other soft tissue sarcomas, they are commonly associated with previous lesions at the site. In the case followed, the feline had no history of previous injury to the affected region. However, as in the present case, the occurrence of extraskeletal osteosarcoma in unusual sites, unrelated to previous lesions, has been described, and in these cases the origin of the neoplasm is associated with totipotent cells. The diagnosis of well-differentiated chondrosarcomas in felines can be determined by the histopathological characteristics of the tumor, requiring the exclusion of primary bone involvement through necropsy and/or imaging to classify the neoplasm as extraskeletal. Radiographic examination, necropsy and histopathology were essential to establish the diagnosis of extraskeletal chondrosarcoma. Keywords: mesenchymal neoplasia, chondrocytes, soft tissue sarcoma.